Nrf2 Participates in M2 Polarization by Trichinella spiralis to Alleviate TNBS-Induced Colitis in Mice - Jin, Xuemin; Bai, Xue; Zhao, Ying; Dong, Zijian; Pang, Jianda; Liu, Mingyuan; Liu, Xiaolei (Frontiers in Immunology, 2021)
Trichinella spiralis induced alternative activated macrophages (M2), leading to protect against Crohn’s disease, known as Th1 –related inflammation, which enhances oxidative stress in the host. However, the relationship of oxidative stress and T. spiralis –mediated immune response is still unknown. In our study, we showed that nuclear factor erythroid 2-related factor-2 (Nrf2), a key transcription factor in antioxidant, participated in M2 polarization induced by T. spiralis muscle larval excretory/secretory (ES) products in vitro. ES –treated M2 were injected intravenously after TNBS challenge and we demonstrated that ES-M could alleviated the severity of the colitis in mice. Adoptive transfer of ES –treated M2 decreased the level of IFN-γ and increased the levels of IL-4 and IL-10 in vivo. However, the capacity of ES –treated Nrf2 KO macrophages to treat colitis was dramatically impaired. ES –treated Nrf2 KO macrophages was insufficient to result in the elevated levels of IL-4 and IL-10. These findings indicate that Nrf2 was required for M2 polarization induced by T. spiralis ES to alleviate colitis in mice.